2016
DOI: 10.1093/mnras/stw2528
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless loss-cone refilling: there is no final parsec problem

Abstract: Coalescing massive black hole binaries, formed during galaxy mergers, are expected to be a primary source of low frequency gravitational waves. Yet in isolated gas-free spherical stellar systems, the hardening of the binary stalls at parsec-scale separations owing to the inefficiency of relaxation-driven loss-cone refilling. Repopulation via collisionless orbit diffusion in triaxial systems is more efficient, but published simulation results are contradictory. While sustained hardening has been reported in sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 50 publications
(65 reference statements)
10
80
0
Order By: Relevance
“…Berczik et al 2006). We find that this result is in good agreement with the previous work of Gualandris et al (2016).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Berczik et al 2006). We find that this result is in good agreement with the previous work of Gualandris et al (2016).…”
Section: Discussionsupporting
confidence: 93%
“…The halo-including sample H5 has far fewer stellar particles at velocities v < w, which explains the lowest hardening rate, even though more stellar mass interacts with the SMBH binary for this simulation sample. We find that this picture is consistent with the study of Gualandris et al (2016): mergers without a DM halo result in a merger remnant in which the SMBH binary evolution depends on the particle number used when N < 10 7 . However, we note that while Khan et al (2011) andPreto et al (2011) reported resolution-independent SMBH binary hardening in mergers without a DM halo, we find resolution-independent hardening rates only in the merger simulations, which use multi-component ICs including a DM halo.…”
Section: Quantifying the Differences In The Hardening Ratessupporting
confidence: 90%
See 3 more Smart Citations